Checklist of mosses of Croatia - Sabovljević M. (Archives of Biological Sciences, 2006)
Published data and available herbaria were used to compile a checklist of Croatian mosses. The flora of bryophytes of Croatia numbers 476 taxa. Among taxa known from Croatia, three are European endemic species and 25 taxa are of pan-European conservation interest.